Analisis Kinerja Website Dinas Komunikasi dan Informatika Menggunakan Metode Pieces - Nurul Huda; Megawaty Megawaty (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
The Diskominfo website is a means of communication to convey various information to the wider community. The existence of a website helps at the same time cover up the government's limitations in the dissemination of various information so that the public does not experience information gaps. This website is analyzed using the Pieces method such as performance, information, economic, control, efficiency, and service by testing using the GT Matrik Tools and Google Transparency Report, while the test results obtained after the analysis are obtained that the average page speed grade is 27%. or in grade F. This means that the quality of the Diskominfo website based on the index generated by Google is still very low, the same thing is also produced by YSlow Grade from Yahoo where the average YSlow Grade is 66% or grade D. The low quality of the web will certainly affect website performance. While testing based on the results of control measurements, the Diskominfo website is safe for public visits. The Diskominfo website has good efficiency, because the existing system can be used properly and can also produce the expected output. In the analysis measurement results, the menu structure that is built can be seen from its initial purpose, which is to provide services to the community, however, this service is still not optimal because the content of the service is not well filled. D. Rendahnya kualitas web tersebut tentu akan mempengaruhi kinerja website. Sedangkan pengujian Berdasarkan hasil pengukuran control, website Diskominfo aman untuk dikunjungi oleh masyarakat.  Website Diskominfo telah memiliki efisiensi yang baik, karena sistem yang ada telah dapat digunakan dengan baik dan juga dapat menghasilkan output yang diharapkan.  Pada hasil pengukuran analisis bahwa struktur menu yang dibangun dapat dilihat tujuan awalnya yaitu dapat memberikan pelayanan kepada masyarakat, Akan tetapi pelayanan ini masih belum maksimal dikarenakan konten pelayanan belum banyak terisi dengan baik.